Signatures in the Stones – The Legacy of Early Medieval Elites on the Territory of Modern Croatia - Maraković, Nikolina (Array, 2007)
Croatian early medieval architectural and sculptural heritage is quite a complex phenomenon, which has been studied extensively from various viewpoints. The authors focussed on a number of early medieval inscriptions which provide information about the donor's name, background and social position, in order to define correlations among their commissions and re-examine them in a wider cultural context. The investors, creators of early medieval cultural landscape, were members of the highest social ranks, who cultivated relationships with ecclesiastical and secular elites across national and political boundaries, and actively participated in a lively exchange of ideas and artistic concepts.